Clinical predictors of hypoxemia in 1-5 year old children with pneumonia - Made Supartha; Putu Siadi Purniti; Roni Naning; Ida Bagus Subanada (Indonesian Pediatric Society, 2010)
Background Pneumonia remains a major killer of under five children. Hypoxemia is the most serious manifestation of pneumonia. The most reliable way to detect hypoxemia is an arterial blood analysis or SPar However, these tools are not widely available; therefore, a simple clinical manifestation should be used as an alternative.Objective To determine clinical predictors of hypoxemia in 1-5 year-old children with pneumonia in Indonesia.Methods This study was conducted between February 2007 to Â August 2008 at Sanglah Hospital, Denpasar, Bali. Sample was selected using a convenient sampling method. Subjects were divided into group of hypoxemia and nonnal saturation. We did clinical examination and SpOz measurement, as the gold standard, simultaneously.Results From 120 subjects